Hubungan antara Verbal Bullying dengan Percaya Diri Siswa Kelas V SD Se-Kecamatan Banjarbaru Utara - Enggar Wibowo, Dodiet; Jumainah; Wulida Makhtuna (Prodi Pendidikan Guru Sekolah Dasar, 2025)
This study aims to determine the relationship between verbal bullying and the self-confidence of fifth-grade elementary school students in North Banjarbaru District. The research employed a quantitative approach with a correlational method. A total of 100 students were selected through purposive sampling from several elementary schools in the area. Instruments used in this study included a verbal bullying scale and a self-confidence scale, both of which had been tested for validity and reliability. The data analysis revealed a negative and significant correlation between verbal bullying and self-confidence, with a correlation coefficient of -0.355 and a significance value of 0.000. The findings suggest that the more verbal bullying a student experiences, the lower their level of self-confidence. These results highlight the importance of school attention to students' psychosocial dynamics, particularly in preventing verbal bullying in elementary school environments. Additionally, efforts to enhance students’ self-confidence must be carried out comprehensively through teacher support, a safe school atmosphere, and parental involvement.